Factors determining competitiveness of paddy industry in Kelantan, Malaysia - Yaacob @ Othman, Azmahani (2019)
Agriculture sector, especially paddy industry has always been given a special priority since rice is the Malaysian staple food. Unfortunately, there were no new areas developed for paddy cultivation. Malaysia has to import 10% to 35% of rice from neighbouring countries to meet the demand. KADA, the granary area in Kelantan was established in 1968. It is the second largest planted area in Malaysia but has been facing low yield of paddy production, surprisingly lower than the country average yield even after 50 years of establishment. Even though the government has allocated billions of Ringgit in order to increase paddy productions and provide various types of support such as R&D, credit facilities, subsidized retail price, guaranteed minimum price, fertilizer subsidies, and irrigation investment, the Kelantan’s paddy production is still considered as inefficient in term of cost and quantity of production. In view of this, there was a need to study the factors that determine the competitiveness of this industry in Kelantan. Porter’s diamond model was used in this study to explain the sources of competitiveness. This model consists of internal and external factors. The internal factors are factor conditions, demand conditions, related and supporting industries and farmers’ strategies while the external factors are government’s role and chances. Target subjects were farmers in Kelantan granary area from four different district, named as Kota Bharu Utara, Kota Bharu Selatan, Pasir Mas and Pasir Puteh. Out of 400 questionnaires distributed, 344 were completely (86%) filled up. All items in the questionnaires were measured using a 10-point interval scale with anchors on 1 = not important and 10 = very important. Partial least Square (PLS) SmartPLS M2 Version 3.0 was used for data analysis. Out of six variables tested, only four variables were significant and able to explain the competitiveness of paddy industry in Kelantan. The variables were factor conditions, demand conditions, supporting industries and chances. Based on Importance-Performance Matrix Analysis (IPMA), the most important factors are factor conditions and chances but proven to be among the least performing factors. So, the government should concentrate and improve these two factors so that the competitiveness level in Kelantan granary area can be increased. The government should also consider to come out with a variety of quality seeds which are adaptable to climate changes to reduce the rate of paddy damage in future. Other than that, the government also might encourage collaboration with higher education institution by sharing their research output with farmers and provide them with training or sharing sessions that can improve their management skill in paddy farming. Periodic evaluation on competitiveness in paddy sector is important to help the government and the farmers to determine the reasons behind their relatively low yield.